How Multi-Step versus One-Step Preparation Method Affects the Physicochemical Properties and Transfection Efficiency of DNA/DODAB:MO Lipoplexes - Oliveira, M. Real; Silva, J. Neves; Oliveira, A. C.; Lucio, Marlene; Gomes, A. F. (Journal of Applied Solution Chemistry and Modeling, 2014)
The consequences for the transfection efficiencies of different lipoplexes preparation methods, largely remain to be explored, but the knowledge of how different experimental approaches can affect the physicochemical properties and transfection efficiency is essential for a proper tailoring of transfection complexes to particular applications. Therefore, the influence of the number of mixing steps (one-step addition versus multi-step addition of liposomes to plasmid DNA (pDNA)) and lipoplex incubation temperature on the final physicochemical properties and transfection efficiency of pDNA/ Dioctadecyldimethylammonium Bromide (DODAB):1-monooleoyl-rac-glycerol (MO) complexes was studied in three distinct DODAB:MO molar ratios: 4:1, 2:1 and 1:1. Dynamic Light Scattering (DLS), Zeta (ζ) Potential, Ethidium Bromide (EtBr) exclusion assays were used to assess the formation, structure and destabilization of the lipoplexes, whereas in vitro transfection assays with pSV-β-gal plasmid DNA were performed to evaluate their transfection efficiency on the 293T mammalian cell line. Results indicate that the morphology of pDNA/DODAB:MO complexes is dependent on the lipoplex preparation method, resulting in particles of distinct size, surface charge and membrane fluidity. These variations are visible during the complexation dynamics of pDNA and continue throughout the profile of pDNA release from pDNA/DODAB:MO lipoplexes upon incubation with Heparin (HEP), as well as in the in vitro transfection assays. The stepwise addition of DODAB:MO vesicles to pDNA decreases the transfection efficiency of the lipoplexes, while the effect of the lipoplex preparation methods is dependent on the MO content.